Nature of active vanadium nanospecies in MCM-41 type catalysts for olefins oxidation - Chanquia, Corina Mercedes; Cánepa, Analía Laura; Winkler, Elin Lilian; Rodríguez Castellon, Enrique; Casuscelli, Sandra Graciela; Eimer, Griselda Alejandra (Elsevier Science Sa, 2016)
Fil: Chanquia, Corina Mercedes. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina